2023
DOI: 10.1002/lary.30611
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Multiport Approach for Exenteration of the Infratemporal Fossa

Abstract: Objective: To demonstrate anatomic relationships pertinent to the endoscopic multiport approach to the infratemporal fossa (ITF). Discuss advantages and limitations of each individual approach.Study Design: Cadaveric study.Methods: Endoscopic and endoscopic-assisted endonasal transpterygoid, sublabial transmaxillary, endoscopic transorbital, and endoscopic transoral approaches to accessing the ITF were completed in five silicone-injected fresh cadaveric specimens (10 sides) with the assistance of 0, 30, and 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Nowadays, the utilization of certain modified open surgical approaches, such as the fronto-orbito-zygomatic approach 10 and the modified zygomatico-transmandibular approach, 11 has also yielded favorable surgical outcomes. However, with the advancement of endoscopic technology, an increasing number of endoscopic approaches been developed, including but not limited to: Caldwell-Luc approach, combined endonasal and Caldwell-Luc approach, 12 distal intraoral approach, 2 endoscopic transorbital approach, 13 prelacrimal recess approach, 14 and so forth. The selection of surgical approaches may vary depending on the extent of the lesion and invasion of surrounding structures, or a combination of multiple approaches can be considered 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the utilization of certain modified open surgical approaches, such as the fronto-orbito-zygomatic approach 10 and the modified zygomatico-transmandibular approach, 11 has also yielded favorable surgical outcomes. However, with the advancement of endoscopic technology, an increasing number of endoscopic approaches been developed, including but not limited to: Caldwell-Luc approach, combined endonasal and Caldwell-Luc approach, 12 distal intraoral approach, 2 endoscopic transorbital approach, 13 prelacrimal recess approach, 14 and so forth. The selection of surgical approaches may vary depending on the extent of the lesion and invasion of surrounding structures, or a combination of multiple approaches can be considered 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Trans-pterygoid endonasal, trans-maxillary sublabial, transorbital endoscopic, and transoral endoscopic approaches to access the infratemporal fossa (ITF) were completed on five cadavers in another study. Indeed, the authors showed that a combination of infratemporal approaches with minimal access can provide adequate exposure of the entire ITF while avoiding some of the morbidity associated with open approaches [75]. However, nowadays the applicability of these approaches in clinical practice remains marginal, due to the nonetheless nonzero morbidities and associated technical challenges.…”
Section: Thetra-portal Endoscopic Approachmentioning
confidence: 99%